2014
DOI: 10.5539/ies.v7n5p39
|View full text |Cite
|
Sign up to set email alerts
|

The Epistemological Perceptions of the Relationship between Physics and Mathematics and Its Effect on Problem-Solving among Pre-Service Teachers at Yarmouk University in Jordan

Abstract: The purpose of this paper was to examine the perception pre-service teachers hold to the nature of the relationship between physics and mathematics. The study examined this relationship in reference to their performance in problem solving and strategies they used. The results of this empirical study suggested that most participants hold a naïve epistemological view that considers mathematics as an instrumental tool for learning physics. The results indicated that these views could be attributed to failure phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Further, some studies, which have challenged students' problem-solving skills, have suggested student-centered instructional practices for problem-solving (Ali, 2019;Saka, 2011;Çalıskan & Selç uk, 2010;Gök, 2012). Moreover, there have also been few comparative studies that handle different features/factors, e.g., grade, science background (Al-Omari & Miqdadi, 2014;Kırılmazkaya, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further, some studies, which have challenged students' problem-solving skills, have suggested student-centered instructional practices for problem-solving (Ali, 2019;Saka, 2011;Çalıskan & Selç uk, 2010;Gök, 2012). Moreover, there have also been few comparative studies that handle different features/factors, e.g., grade, science background (Al-Omari & Miqdadi, 2014;Kırılmazkaya, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mathematics is considered as the language in which the Physics theories are built by employing Mathematical symbols and operations to make equations and representations in the world of Physics completely meaningful (Redish, 2005). In short, relationship between these two streams is identified to be noteworthy by both physicist and Mathematicians (Al-Omari & Miqdadi, 2014) due the technical, structural and communicative roles of Mathematics in Physics (Ataide & Greca, 2013;Pospiech, 2015).…”
Section: Introductionmentioning
confidence: 99%